The Effect of Participatory Leadership on Turnover Intention Through Satisfaction As Mediation Variable - Arjuna Mutakkabir; Aniek Rumijati; Mursidi Mursidi (Jurnal Manajemen Bisnis dan Kewirausahaan (JAMANIKA), 2022)
This study aims to determine the description of leadership, employee satisfaction, and turnover intention and analyze the influence of participatory leadership on turnover intention through satisfaction as a mediating variable at coffee shops around Omah Campus. The research method used is quantitative which is collected by questionnaire through a Likert scale with 5 levels. The data that has been collected is then analyzed by Partial Least Square (PLS) using the SmartPLS software version 3. The results of the PLS analysis show that the variables of participatory leadership and employee satisfaction are in the high category, while the turnover intention is in the low category. Furthermore, it is known that the employee job satisfaction variable can significantly mediate the influence of the participatory leadership variable on turnover intention.